PENGARUH KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDARDS DAN AUDIT DELAY: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Daniswara, Ricko; Kiswara, Endang (Diponegoro Journal of Accounting, 2015)
The financial report is a financial communication medium between the company management with external parties or stakeholders. The good financial report is a report that meets the relevant elements. The relevance of such financial statements may be reviewed by how timely financial statements are reported. This timeliness can be seen from the audit delay, ie the period between the closing date until the date of grant by an auditor opinion. This study was conducted to test empirically the extent of convergence of IFRS, company size, and quality auditors on the audit delay effect on manufacturing companies listed in Indonesia Stock Exchange.The data used in this research is secondary data, in the form of annual financial statements of 66 companies manufacturing samples listed in the Indonesia Stock Exchange in 2012. To prove the hypothesis that had been developed, then tested the simple linear regression, which begins with a classical assumption test , Regression model in this study declared to have passed the test classic assumptions.Hypothesis testing using simple regression concluded that the convergence of IFRS and control variable of company size have no effect on audit delay, whereas the control variable of quality of the auditor has the significant effect on audit delay.